EFFECT OF SYNTHETIC PYRETHROID PERMETHRIN ON CHOLINERGIC MECHANISMS IN DIFFERENT REGIONS OF THE BRAIN IN ALBINO MICE - C.OBULPATHI; S.V. RAVIKANTH; P. JACOB DOSS (International Journal of Pharma and Bio Sciences, 2013)
Latest pesticide monitoring results suggests that there is a shift in residential pesticide exposure from organophosphorous insecticides to pyrethroid insecticides. Although it is well known that pyrethroid insecticides are potential neurodevelopmental toxicants, research pertaining to their effect, especially permethrin, has not been carried out in mice. In the present study we report the effect of sublethal dose of permethrin (84 mg/kg body weight), on the cholinergic mechanisms in different regions of brain in the Albino mice. There is a steady decline in the AChE activity in different regions of the brain of permethrin, exposed mice. An increase in the ACh activity was noticed in all the regions of the brain of permethrin exposed animals. The present results suggest that mechanism of ACh synthesis is seriously affected by the intoxication of permethrin. The effect of permethrin was more in 30 days when compared to 10 days.